The problem of money : African agency and Western medicine in northern Ghana - Bierlich, Bernhard, 1963- (Monographs in German history., 2007)
"Based on long-term medical anthropological research in northern Ghana, the author analyses issues of health and healing, of gender, and of the control and use of money in a changing rural African setting. He describes the culture of medical pluralism, typical for neo-colonial states, and people's choices of 'traditional' (local) medicine (plants and sacrifices), Islamic medicine (charms and various written solutions) and 'modern' therapy (biomedicine, in particular western pharmaceuticals). He concludes that the rural-urban divide is a fiction, linked by a postcolonial, capitalist discourse of local markets, regional economies and national structures, which frequently emerge in local African settings but often originate in global and multinational markets."--Jacket